Immunostaining of lectin glycoconjugates in primary and metastatic canine mammary neoplasms - Bezerril, Juliana E.; Marcusso, Paulo F.; Claudiano, Gustavo S.; Yunis-Aguinaga, Jefferson; Petrillo, Thalita R.; Alessi, Antonio C. [UNESP] (Springer Nature, 2020)
The aim of this study was to investigate glycoconjugate immunostaining of the biotinylated lectins: UEA - Ulex europaeus (gorse), PNA - Arachis hypogaea (peanut), HPA - Helix pomatia (Roman snail), and DBA - Dolichos biflorus, in normal mammary glands (control; n = 7), mammary neoplasms (n = 111), and mammary neoplasm metastasis (n = 10). One hundred twenty-eight mammary gland tissue samples were used; 7 samples without history of neoplasms (control). The remaining samples (121) were mammary neoplasms or metastasis. In all cases (UEA, HPA, PNA, and DBA), the binding to normal epithelium was uniform. The immunohistochemical marking was in the membrane and cytoplasm of epithelial cells in most of the cases. Large variations of binding between cell membranes, cytoplasm, and nuclei occurred in the neoplastic and metastatic tissues. Though lacking statistical differences, UEA, PNA, HPA, and DBA lectins revealed different marking patterns between tissues, being metastatic foci less marked in comparison with normal and neoplastic mammary gland tissues. In addition, there were no significant differences in the immunostaining of lectins between tumors where HPA was the most expressed in papillary carcinoma I, PNA in papillary carcinoma II, DBA in carcinosarcoma, and HPA and DBA in mixed carcinoma. It was concluded that the lectins have diagnostic potential and they have been useful for differentiation between normal and neoplastic breast tissue of metastatic foci in mammary tumor in dogs.
Keywords: Diagnosis of neoplasms; Lectin histochemistry; Oncology; Tumor